Travel‐weary to travel‐worry: the epidemiology of injury‐related traveller deaths in Australia, 2006‐2017 - Lauren Miller; Richard C. Franklin; Kerrianne Watt; Peter A. Leggat (Elsevier, 2022)
Abstract Objective: To explore injury deaths in international and domestic interstate travellers, together with those newly arrived to Australia. Methods: A population‐based cohort study of all injury‐related deaths between 1January 2006 and 31 December 2017 registered with Births Death and Marriages in Australia was conducted using Australian Bureau of Statistics' (ABS) Cause of Death information. Population data on travellers were obtained from Tourism Research Australia. Results: There were 4,503 injury‐related traveller deaths (domestic interstate:3,055; international:934; new arrivals:514). The average annual age‐standardised mortality rates in domestic interstate travellers was 0.75 per 100,000, compared with 2.22 per 100,000 in international travellers. Leading causes of injury‐related death were land transport incidents (n=1495, 33.2%), self‐harm (n=786, 17.5%) and falls (n=513, 11.4%), with differences in mechanism by state/territory, traveller type and age group. Intentional self‐harm was common amongst all visitor types, however, it was the primary cause of death in new arrivals Conclusion: Age‐standardised mortality rates were almost three‐fold higher in international than domestic travellers. New arrivals, international and domestic travellers have different injury profiles, and each require specific prevention strategies. Implications for public health: While COVID has restricted travel to and within Australia, this has provided an opportunity for exploration, reflection, and consideration of risk factors for travellers, and to develop targeted injury prevention strategies for visitor types, so travel experience can be optimised and the magnitude of harm can be reduced.